SOSIALISASI PENTINGNYA PENDIDIKAN TINGGI SEBAGAI IMPLEMENTASI PASAL 31 AYAT 1 UUD 1945 DI SMP YATRIMAS - Makiin, Inda Dzil Arsyi; Salima, Luthfia Qolbi; Qudratuddarsi, Hilman; Putri, Thyrafi Amelia (LPPM Universitas Nusa Mandiri, 2025)
The interest of the Indonesian people in continuing their education to higher education levels is still relatively low, at only 6.68% of the total population of Indonesia (18.7/280 million people). Lampung is one of the provinces facing this issue, with data from 2023 showing that 77.36% of high school graduates in Lampung Province do not continue their education to higher education levels. Ringin Jaya Village is one of many villages in Lampung Province where students have a low interest in continuing their education to higher education levels. The main factors causing this are the limited number of schools, the family's economic conditions, and the lack of understanding regarding the importance of higher education. However, the 1945 Constitution of the Republic of Indonesia Article 31 Paragraph 1 mandates that